Survey method of health care providing to children less than one year in health ‎departments - zahra mokhtari; noshaz mir haghjo; shadman reza masuoleh; anooshirvan kazemnezhad (Journal of Holistic Nursing and Midwifery)
Introduction: Health care providing to children with optimal quality is part of maternal and ‎child health program that its quality performance causes reduced mortality, complication and ‎health maintenance. Thus evaluating these care and promotion of health care providers, ‎performance and its quality certainly will have effective role in maternal child well – being‏.‏‎